Hedonic and motivational responses to food reward are unchanged in rats with neuropathic pain. Issue 12 (December 2016) - Okun, Alec; McKinzie, David L.; Witkin, Jeffrey M.; Remeniuk, Bethany; Husein, Omar; Gleason, Scott D.; Oyarzo, Janice; Navratilova, Edita; McElroy, Brian; Cowen, Stephen; Kennedy, Jeffrey D.; Porreca, Frank
Abstract : Abstract: Rewards influence responses to acute painful stimuli, but the relationship of chronic pain to hedonic or motivational aspects of reward is not well understood. We independently evaluated hedonic qualities of sweet or bitter tastants and motivation to seek food reward in rats with experimental neuropathic pain induced by L5/6 spinal nerve ligation. Hedonic response was measured by implantation of intraoral catheters to allow passive delivery of liquid solutions, and "liking/disliking" responses were scored according to a facial reactivity scale. Spinal nerve ligation rats did not differ from controls in either "liking" or "disliking" reactions to intraoral sucrose or quinine, respectively, at postsurgery day 21, suggesting no differences in perceived hedonic value of sweet or bitter tastants. To assess possible motivational deficits during acute and chronic pain, we used fixed- and progressive-ratio response paradigms of sucrose pellet presentation in rats with transient inflammatory or chronic neuropathic pain. Assessment of response acquisition and break points under the progressive ratio schedule revealed no differences between sham and spinal nerve ligation rats for up to 120 days after injury. However, rats with inflammation showed decrements in lever pressing and break points on days 1 and 2 after complete Freund adjuvant injection that normalized by day 4, consistent with transient ongoing pain. Thus, although acute ongoing inflammatory pain may transiently reduce reward motivation, we did not detect influences of chronic neuropathic pain on hedonic or motivational responses to food rewards. Adaptations that allow normal reward responding to food regardless of chronic pain may be of evolutionary benefit to promote survival. Abstract : Hedonic qualities of sweet or bitter tastants and motivation for food reward are not altered in rats with experimental chronic neuropathic pain.